Development of Online Materials in the Subject Course Analysis and Data Utilization on the NFPPB Training Center - Ma'ruf, Armen; Ibrahim, Nurdin; Syahrial, Zulfiati (Universitas Negeri Padang, 2020)
This research is research and development (R&D). The purpose of this research is to develop online material for the Analysis and Data Utilization Subject Course in the NFPPB Training Center. The study was conducted at the NFPPB with the aim of participants of the Family Planning Village Operationalization Technical Training. The research method refers to the Allan Jolliffe development model. The results of the development of online material for Analysis and Data Utilization can be accessed at URL http://www.annangguru.com/elearning. Online material developed using Moodle application software with moove model. The product development procedure is carried out according to the reference model of the Allan Jolliffe development. The step-by-step review process is carried out by material experts, media experts, and instructional design experts. To the target of the study conducted the one-on-one test, small group test, and field test. Evaluation is carried out until the summative evaluation stage by calculating the N-Gain Score. The results of the summative evaluation stated that the online material for the analysis and data utilization was effective in improving the learning outcomes of trainees in the NFPPB Training Center.Keywords: Web-Based Course, Development Studies, Online Materials